Preparation and evaluation of tumor-targeting peptide−oligonucleotide conjugates - Mier, Walter; Haberkorn, Uwe; Eisenhut, Michael (Bioconjugate chemistry, 2000)
Enormous progress has been made in the development of antisense oligodeoxynucleotides (ODNs) as therapeutic agents inhibiting gene expression. Unfortunately, the therapeutical application of ODNs is still held back because of the low cellular uptake and the lack of specific transport into particular cells. In this paper, we report a drug-targeting system using somatostatin receptors (SSTRs) which are overexpressed in various tumors. Phosphorothioate ODNs were covalently linked to Tyr3−octreotate, an analogue of somatostatin. The peptide was assembled by solid-phase synthesis, oxidized to form the cyclic disulfide, and subsequently derivatized with a N-terminal maleimido functionality. 5‘-Thiol derivatized phosphorothioate-ODNs directed against the protooncogene bcl-2 were conjugated to this maleimido-modified peptide. Binding studies revealed that the conjugates retain specific binding with nanomolar affinities to SSTRs (IC50-values between 1.83 and 2.52 nM). Furthermore, melting studies with complementary DNA revealed that the terminal conjugation of the ODNs did not significantly affect their hybridization affinity.
Gesehen am 09.02.2021